Pendidikan lingkungan berbasis experiential learning untuk meningkatkan literasi lingkungan - Hayati, Riza Sativani (Universitas Negeri Yogyakarta, 2020)
Damage to the ecosystem and decline in the amount of biodiversity continues. Ecosystem damage due to human activities has become a global problem. This destructive activity reflects the low of the community's environmental literacy. Environmental education can be a solution to improve community's environmental literacy. The objectives of environmental education are (1) awareness; (2) knowledge; (3) attitude; (4) skills; and (5) participation. One effective method in environmental education is based on experiential learning. This article aims to explain the concept of environmental education based on experiential learning which can be an alternative integration of environmental education in schools. This article discusses the urgency of environmental literacy, how environmental education can improve environmental literacy, and detailed concepts of how to implement environmental education based on experiential learning in schools. Experiential learning-based environmental education means instilling Kolb's learning cycle in learning and environmental education programs. The Kolb cycle consists of: (1) Concrete Experience; (2) Observation and Reflection; (3) Forming Abstract Concept; (4) Testing in New Situation. Experiential learning based environmental education will provide provisions for students to be able to design pro-environment actions or participate in providing solutions to environmental problems.